Development of E-module Using Bengkulu Contexts to Improve Literacy Skills of Junior High School Students - Agus Susanta; Hari Sumardi; Zulkardi Zulkardi (Universitas Sriwijaya, 2022)
This research aims to produce a valid and practical e-module using the Bengkulu context that potentially affects students' literacy skills to understand the materials of patterns and number sequences. This research employed a research and development method. The development stages refer to Plomp’s five developments: (1) preliminary research, (2) the prototype-making stage, and (3) the assessment stage. The subjects of this research were 24 eighth-graders of SMP Negeri 6 Bengkulu City. The data collection techniques of this research were observation and test. Meanwhile, the research instruments were validation instruments, questionnaires, and literacy test questions. Validity analysis was conducted descriptively and consisted of an analysis of validity, practicality, and literacy test results. The average score of the expert validity is 0.64 and meets the valid criterion. The e-module has a practical category with a score of 3.55, and the requirements are very practical. The e-module has impacted students' literacy skills with an average score of 74.25 or good criteria. Moreover, e-module using Bengkulu context problems can encourage students to improve their mathematical literacy skills.